Labour markets and wages in Australia in 2011 - Jefferson, Therese; Preston, A. (Blackwell Publishers, 2012)
In a context of international economic uncertainty and uneven domestic economic performance, labour market outcomes showed considerable diversity. Wide-ranging outcomes in employment numbers, patterns of full-time and part-time work, labour utilization, and changes in earnings were evident both across and within industries. Men’s full-time employment appears to be one labour market area that is experiencing particular decline as casualization of the workforce continues and men’s traditional industries of employment experience subdued economic growth. Women’s employment appears to be faring relatively well in terms of growth, but large and persistent gender pay gaps remain evident in particular feminized industries, including financial and insurance services and health and social assistance. Predictions made earlier this decade that population ageing might ensure relative stability in employment among younger workers have not yet been fulfilled. Younger workers continue to experience relatively high levels of unemployment and underutilization, with the immediate employment experiences of younger men being relatively unfavourable compared with younger women in the workforce.